A stimulus‐contingent positive feedback loop enables IFN‐β dose‐dependent activation of pro‐inflammatory genes - Catera L Wilder; Diane Lefaudeux; Raisa Mathenge; Kensei Kishimoto; Alma Zuniga Munoz; Minh A Nguyen; Aaron S Meyer; Quen J Cheng; Alexander Hoffmann (Molecular Systems Biology)
Abstract Type I interferons (IFN) induce powerful antiviral and innate immune responses via the transcription factor, IFN‐stimulated gene factor (ISGF3). However, in some pathological contexts, type I IFNs are responsible for exacerbating inflammation. Here, we show that a high dose of IFN‐β also activates an inflammatory gene expression program in contrast to IFN‐λ3, a type III IFN, which elicits only the common antiviral gene program. We show that the inflammatory gene program depends on a second, potentiated phase in ISGF3 activation. Iterating between mathematical modeling and experimental analysis, we show that the ISGF3 activation network may engage a positive feedback loop with its subunits IRF9 and STAT2. This network motif mediates stimulus‐specific ISGF3 dynamics that are dependent on ligand, dose, and duration of exposure, and when engaged activates the inflammatory gene expression program. Our results reveal a previously underappreciated dynamical control of the JAK–STAT/IRF signaling network that may produce distinct biological responses and suggest that studies of type I IFN dysregulation, and in turn therapeutic remedies, may focus on feedback regulators within it.